UCE Birmingham conservatoire: CD sampler - Royal Birmingham Conservatoire (United Kingdom) (Birmingham UCE Birmingham conservatoire, 2006)
- Reich- Harvey- Duruflé- Fletcher- Bartok- Cutler- Dvorak- Siegel- Ravel